The efficacy of anti-avoidance provisions and control mechanisms in the Tax Administration Act 28 of 2011 and Income Tax Act 58 of 1962 in relation to the nature and utilisation of crypto currencies in the current economic culture - Fritz, Carika (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.